Psycho-Motor Development and Social Development Impact of Sports - Emre Yıldız; Zeynep Çetin (Hacettepe Üniversitesi Sağlık Bilimleri Fakültesi Dergisi, 2018)
Sports is a phenomenon involving movement and expanding the social environment of individuals. Individuals have the opportunity to observe some social skills about how to behave in a social environment through sports. Sport with motion, supports motor skills at the same time. Motor skills for children are also pre-school; It is important for the role and happiness of the games. These skills in the pre-school period can be directed to the branches in the direction of the child's interest during the school period. When children play sports, both motor skills and social skills will be supported. At the same time, they will have the opportunity to meet more people and share the same social environment and thus they will have the opportunity to acquire skills such as interpersonal communication, group participation, self-awareness and recognition of limitations, experiencing and learning feelings such as winning and losing, self-expression, self-confidence while playing sports. In addition to their developmental contribution to sport, they also play an important role in enabling people to be productive, healthy and happy in their communities. Based on the above information, this article examines the interaction of sports with psychomotor and social development.